Plan de ejercicios físicos para mejorar la resistencia de los jugadores del club Venecia de la ciudad de Babahoyo - BORJA FABRE CARLOS ANTONIO (2024)
The objective of this study is to develop and evaluate a physical exercise plan to improve the resistance of the players of the Club Sport Venecia de Babahoyo. Endurance is crucial to soccer performance, allowing players to maintain a high level of effort during matches. The research will focus on how a specifically designed exercise plan can improve the endurance of players, taking into account the characteristics and limitations of the equipment and its environment. The methodology used will be mixed, combining quantitative and qualitative approaches. Standardized physical tests, such as the Cooper Test and the Yo-Yo Test, will be applied to measure the aerobic and anaerobic capacity of the players. In addition, open interviews and group discussions will be carried out to collect the perceptions of the players and coaches about the exercise plan. The population under study consists of 32 players, from which a representative sample of 30 players will be selected through simple random sampling. Data collection techniques will include structured observation, surveys, physical tests, and interviews. The research will be carried out in several phases: preparation, execution, data collection, analysis and presentation of results. Compliance with ethical aspects will be emphasized, ensuring informed consent, confidentiality and protection of participants.